CLINICAL ASPECTS AND MORPHOFUNCTIONAL FEATURES OF THE THYROID GLAND - JO’RAYEVA FARANGIZA ERKINOVNA (TADQIQOTLAR, 2025)
Abstract: The influence of thyroid hormones on the formation of the brain has been shown by numerous classical studies. However, the presence of neurons, astrocytes and microglia in the brain The 2021 release of TRα and TRβ receptors was associated with low TSH levels and poorer performance on tests of cognitive development in older adults with a mean age of (49.5 ± 7.4) years, without overt thyroid dysfunction.